Moral Distress among Nurses in Developing Countries of Asia: A Systematic Review - Joseph, Sonia; Khair Tunio, Hanna; Shahzad, Samuel; Abbass, Eraj; Nangrejo, Ruqaya (Journal of Liaquat University of Medical & Health Sciences, 2022)
Compromising moral values and professional reliability can cause moral distress among nurses. Nurses have to play a significant role in the profession of care providers. They have to use their moral beliefs to make important decisions when providing care to patients. Nurses’ struggle for professional compatibility and success has been seen for many years. They have an inner strive to be recognized for the hard work in their profession. This systematic review aims to examine existing literature on moral distress among nursing working in developing countries of Asia from September 2010 to September 2021. The total number of articles meeting the critical appraisal criteria was 19. The articles selected were quantitative (n=12), Qualitative (n= 4), Mixed-method (n=2) and literature review (n=1). Several studies were conducted to measure the frequency and intensity of moral distress and its related factors among nurses. Most scientific studies have shown consistency in measurements of moral distress. Studies have shown that nurses facing moral distress express their distress through various physical and psychological responses. Further several studies have shown moral distress is more related to workload and work-related stress among nurses. Ethical values are the segment of organizational culture, and space for ethical values, if not provided to the nurses, may lead to moral distress among nurses. Workload and unnecessary orders from supervisors and physicians further increase nurses’ moral distress. Institutes need to understand their responsibility in producing an ethical distress environment. KEYWORDS: Moral distress, Ethical values, Nurses, Workload, Professional environment